The Syllabi of Portuguese Apprenticeship Courses and Opportunities to Access Higher Education: Critical Perspectives of IVET Students - Doroftei, Alexandra; Marques da Silva, Sofia (Journal of Technical Education and Training, 2024)
Portugal, Initial Vocational Education and Training (IVET) has a negative public image, which is partly due to perceptions about course syllabi and the low number of former IVET students who go on to higher education. We aimed to analyse the perspectives of IVET students on the syllabi of a Portuguese IVET modality, specifically the apprenticeship courses. Our focus was on the knowledge conveyed in the sociocultural and scientific components, as well as the possibility of accessing higher education. The analysis was made within the framework of Michael Young’s “powerful knowledge” and McGregor’s “meaningful education” concepts. Data analysis was based on 54 semi-structured interviews with apprenticeship course students from nine training centres in northern Portugal. A deductive-inductive content analysis supported by NVivo software was used. The knowledge acquired in the apprenticeship courses is compared with its counterpart of general upper secondary education. The results point out that overall, the participants mention that they find the subjects of the sociocultural and scientific components of the apprenticeship courses’ syllabi to be easy, simplified, and summarised. These features discourage some students who expect to extend their knowledge. For others, the applicability of the knowledge acquired to “real life” is valued. As far as access to higher education is concerned, some students are aware that the knowledge acquired in the courses hampers their ability to take the national access exams, while others are not aware of these constraints. Paying for private lessons to study for the exams is a mentioned possibility. In conclusion, apprenticeship courses’ sociocultural and scientific syllabi are based on a very low academic level, comparable to that of lower secondary education. This levelling down impairs students to perform well in the national exams that give access to higher education. A real equivalence of knowledge between the sociocultural and scientific components of apprenticeship courses and the general component of general education would be beneficial for that. It could also promote greater parity of esteem between vocational and general education, lessening the negative perception of IVET that persists in Portugal.